2014
DOI: 10.1097/jnn.0000000000000078
|View full text |Cite
|
Sign up to set email alerts
|

Attention and Memory Deficits in Breast Cancer Survivors

Abstract: Breast cancer survivors (BCSs) commonly report deficits in attention and memory, cognitive functions crucial for daily optimal functioning. Perceived deficits are reported before, during, and after adjuvant therapy and affect quality of life throughout survivorship. Deficits of attention and memory are particularly disruptive for BCSs working or attending school who report that subtle impairment diminishes their confidence and their performance at all levels of occupation. Chemotherapy and endocrine therapy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Some evidence suggested that hormonal changes during specific treatments do not provoke cognitive decline in patients BCSs in the first years from diagnosis [31]. The occurrence of severe perceived cognitive deficits have been noted, above all in attention and memory, and worse QoL in BCSs who were undergoing adjuvant therapy, which are disruptive for BCSs in their work life because of lack of performance [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence suggested that hormonal changes during specific treatments do not provoke cognitive decline in patients BCSs in the first years from diagnosis [31]. The occurrence of severe perceived cognitive deficits have been noted, above all in attention and memory, and worse QoL in BCSs who were undergoing adjuvant therapy, which are disruptive for BCSs in their work life because of lack of performance [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…If not addressed, these deficits can persist throughout survivorship and decrease quality of life in realms including home, work, and community. Possible strategies for alleviating cognitive deficits include healthy lifestyle changes (cognitive prescriptions), complementary therapies, pharmacologic treatments, cognitive remediation therapy, or a combination of these options (Frank et al, 2014). Vance, Eagerton, Harnish, McKie-Bell, and Fazeli (2011) suggest that healthy living including adequate sleep, good nutrition, intellectual activity, physical exercise, and socialization has positive effects in both healthy aging and in patients with HIV/AIDS.…”
Section: Interventions For Cognitive Deficits In Bcsmentioning
confidence: 99%
“…The aim is to reduce the number of new cancer cases, as well as the illnesses, disabilities, and deaths caused by cancer (U.S. Department of Health and Human Services [DHHS], 2017). Chemo brain, as a result of chemotherapy treatment of women diagnosed with breast cancer, is an important, and little understood phenomena both for the women using the healthcare system and for the professional nurses who are their major healthcare providers (Frank, Vance, Jukkala, & Meneses, 2014). Symptoms of chemo brain that significantly impact the quality of life for women with breast cancer who are receiving chemotherapy are evident in their daily lives; however, patients with manifestations of chemo brain often do not receive validation, treatment or education about these symptoms (Grober, 2002).…”
Section: Problemmentioning
confidence: 99%